2020
DOI: 10.3390/molecules25184279
|View full text |Cite
|
Sign up to set email alerts
|

Quinoline-Based Molecules Targeting c-Met, EGF, and VEGF Receptors and the Proteins Involved in Related Carcinogenic Pathways

Abstract: The quinoline ring system has long been known as a versatile nucleus in the design and synthesis of biologically active compounds. Currently, more than one hundred quinoline compounds have been approved in therapy as antimicrobial, local anaesthetic, antipsychotic, and anticancer drugs. In drug discovery, indeed, over the last few years, an increase in the publication of papers and patents about quinoline derivatives possessing antiproliferative properties has been observed. This trend can be justified by the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
23
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(25 citation statements)
references
References 137 publications
1
23
0
1
Order By: Relevance
“…105 Recent work focused on compounds effective on the c-Met, VEGF and EGF receptors, pivotal targets for the activation of important carcinogenic pathways (Ras/Raf/ MEK and PI3K/AkT/mTOR). 106 A pictorial representation of the cross talk among the EGFR, VEGFR, and c-Met signaling pathways is shown in Fig. 20.…”
Section: Combined Signaling Pathways In Oncologymentioning
confidence: 99%
“…105 Recent work focused on compounds effective on the c-Met, VEGF and EGF receptors, pivotal targets for the activation of important carcinogenic pathways (Ras/Raf/ MEK and PI3K/AkT/mTOR). 106 A pictorial representation of the cross talk among the EGFR, VEGFR, and c-Met signaling pathways is shown in Fig. 20.…”
Section: Combined Signaling Pathways In Oncologymentioning
confidence: 99%
“…Therefore, to identify potential MEK1 inhibitors with good efficacy, molecular docking, long‐term molecular dynamics (MD) simulations, and molecular mechanics Poisson–Boltzmann surface area (MM‐PBSA) studies were implemented. Previous studies as well as the patents have claimed several quinoline derivatives as a prosperous scaffold for cancer and a noncompetitive inhibitor of MEK1 18–23 . In this study, we have selected 37 in‐house quinoline derivatives to discover allosteric inhibitors of MEK1 in comparison with four reference molecules (three identified inhibitors and one cocrystal) 24 …”
Section: Introductionmentioning
confidence: 99%
“…Quinoline is naturally present in many alkaloids having potent antitumor activity, for example, camptothecin 14 (Figure 1). Quinoline scaffold and its related derivatives represent a broad spectrum of pharmacological activities, especially in drug discovery of new anticancer agents [15][16][17][18] . Food and Drug Administration (FDA) has approved various quinoline small molecules acting as protein kinases inhibitors for clinical uses in cancer disease [19][20][21][22] (Figure 1).…”
Section: Introductionmentioning
confidence: 99%
“…The occurrence of the nitrogen atom in the quinoline nucleus withdraws electrons by resonance and interferes with the equal distribution of π electron density. It has been reported that the quinoline nucleus has a great tendency to bind to the active site of various proteins via the formation of hydrogen bonds with its nitrogen atom and π–π stacking complexes with complementary amino acid residues 15 , 16 .…”
Section: Introductionmentioning
confidence: 99%